Microbiome Profiles of Commercial Broilers Through Evisceration and Immersion Chilling During Poultry Slaughter and the Identification of Potential Indicator Microorganisms - Handley, John A.; Park, Si Hong; Kim, Sun Ae; Ricke, Steven C. (Frontiers in Microbiology, 2018)
Commercial poultry abattoirs were evaluated to determine the efficacy of the multi-hurdle antimicrobial strategy employed to reduce the microbial load present on incoming broilers from the farm. As next generation sequencing (NGS) has been recently employed to characterize the poultry production system, this study utilized 16S High throughput sequencing (HTS) and quantitative plating data to profile the microbiota of chicken carcasses and determine the efficacy of the multi-hurdle antimicrobial system. Aerobic plate count (APC) and Enterobacteriaceae (EB) microbial counts were quantified from whole bird carcass rinsates (WBCR). The remaining rinsates underwent microbiome analysis using 16S rRNA gene fragments on an Illumina MiSeq and were analyzed by Quantitative Insights into Microbial Ecology (QIIME). The key stages of processing were determined to be at rehang, pre-chill, and post chill as per the Salmonella Reduction Regulation (75 Fed. Reg. 27288-27294). The APC microbial data from rehang, pre-chill, and post chill were mean log 4.63 CFU/mL, 3.21 CFU/mL, and 0.89 CFU/mL and EB counts were mean log 2.99 CFU/mL, 1.95 CFU/mL, and 0.35 CFU/mL. Next generation sequencing of WBCR identified 222 Operational Taxonomic Units’ (OTU’s) of which only 23 OTU’s or 10% of the population was recovered post chill. Microbiome data suggested a high relative abundance of Pseudomonas at post chill. Additionally, Pseudomonas, Enterobacteriaceae, and Weeksellaceae Chryseobacterium have been identified as potential indicator organisms having been isolated from all processing abattoirs and sampling locations. This study provides insight into the microbiota of commercial broilers during poultry processing.